Sustainability and destination branding: a review of research trends - Sita , Dewi Kusumaningrum (Turisztikai és Vidékfejlesztési Tanulmányok, 2023)
Branding plays an essential role in communicating and maintaining the sustainability value of a tourist destination. Therefore, some research attempt to empirically incorporate sustainability in tourism related research. Nevertheless, a bibliometric study investigating the progress and trend of research on sustainability and destination branding is still limited. This study investigates state-of-the-art research on sustainability and destination branding using the bibliometric analysis method. A sample of 329 documents published on Scopus is processed and analyzed based on performance analysis and science mapping techniques in the bibliometric approach, particularly the citation and co-word analysis. The VOSviewer software helps understand the research trends and opportunities of research on sustainability and destination branding through the network, overlay, and density visualization. In brief, this study delivers an understanding of the critical aspects of the bibliometric study, such as the context, the content, and research opportunities concerning research of sustainability and destination branding.